Barriers to Psychosocial Care in Nursing Homes as Reported by Social Services Directors. Issue 7 (3rd October 2021) - Roberts, Amy Restorick; Smith, Kevin; Bern-Klug, Mercedes; Hector, Paige
ABSTRACT: This study identifies social services directors' perceptions of major barriers to psychosocial care and examines the structural factors associated with these barriers. Data were merged from the 2019 National Nursing Home Social Services Directors Survey and CMS's Nursing Home Compare. A hierarchical linear regression predicts overall barriers. Nine binary logistic regressions predict specific barriers. Common major barriers include "insufficient number of nurse aide staff" (31%), and "having to do things other people could do" (30%). Overall barriers to psychosocial care decreased as directors' years of experience increased, the number of staff members in social services increased, and less time was spent on short-stay residents. Departments with one staff member (compared to 3+) have a 300% greater likelihood of perceiving a major barrier in social services staffing, pressured discharge of short-stay residents, and residents' socioemotional needs are treated as less important than medical/nursing needs. Directors had a 59%-239% greater likelihood of perceiving a major barrier across six of the nine barriers when 50% or more of social services staffing is devoted to short-stay residents. To improve psychosocial care, federal guidelines should ensure adequate staffing levels differentiated by resident needs across short- and long-term care.